STUDI EKSPERIMEN TEKNOLOGI PEMBANGKIT LISTRIK TENAGA ARUS LAUT (PLTAL) MENGGUNAKAN SAVONIUS BACH ROTOR - Yusiran Hikmat; Erwin Erwin (Komunikasi Fisika Indonesia, 2019)
Design and experiment of ocean current power generation system have been carried out using the Bach Savonius rotor. In this research, the influence of the velocity of ocean currents, the number of turbine blades, and the blade arc angle of the generator output power are studied. The results showed that the turbine output power is strongly influenced by the velocity of ocean currents where the velocity values of ocean currents varied in the range 0,63-1,98 m/sec. The maximum elctrical power of the turbine occurs at a current velocity of 1,98 m/sec of 26,88 Watts. The number of turbine blades has a significant effect on turbine output power. The turbine reaches maximum power is found in the rotor with a number of 3 blades with a power coefficient of 0,1176 on the tip speed ratio of 0,359. The blade arc angle is varied at angles of 90˚, 135˚ and 165˚. The blade arc angle 135˚ gives the best performance with a power coefficient of 0,102 on the tip speed ratio of 0,298.